-PLUS prehospital mass-casualty triage: a strategy for addressing unusual injury mechanisms. - Neal DJ; Barbera JA; Harrald JR; Neal, Daniel J; Barbera, Joseph A; Harrald, John R (Prehospital & Disaster Medicine)
Introduction: Simple Triage and Rapid Treatment (START) and more recently developed prehospital casualty triage algorithms are widely used, in part because they are easy to teach and learn, and can be performed rapidly. Every rapid triage protocol has inherent, significant limitations: (1) no mechanism of injury (MOI) considerations; (2) limited assessment points; and (3) no refinement in truly mass-casualty situations where transport of "minor" or "moderate" patients may be delayed.Hypothesis: When rapid initial triage protocols are utilized, a significant triage deficiency ("under-triage") may occur when "minor" or "moderate" casualties actually are more severely injured than initially triaged. Some MOI produce casualties with subtle or latent (i.e., hidden or delayed) signs and symptoms not considered in the commonly used prehospital triage algorithms. This research did not focus on START or other initial triage screening methods. Instead, it focuses on developing follow-on triage guidance to more specifically prioritize "delayed transport" casualties based upon signs and symptoms related to their MOI.Methods: Using expert opinion and accepted clinical criteria, triage algorithms were developed to re-evaluate patients triaged to "minor" and "moderate" cohorts. A detailed literature search produced a draft list of relevant signs and symptoms for each selected MOI. The lists then were evaluated by a multi-disciplinary panel of experts via an anonymous, mail-based Delphi method. The input shaped triage algorithms for each selected MOI, which then were subjected to a second stage Delphi process.Results: Consensus was achieved using the Delphi method. The algorithms extend patient assessment beyond the rapid initial triage protocols and incorporate triage criteria specific to each selected injury mechanism or condition: (1) penetrating injuries; (2) unconventional MOI (burns, blast, chemical, radiation); (3) smoke and other inhalation exposure; and (4) injuries with concomitant pregnancy. The full list of triage protocols is designated by the acronym "-PLUS".Conclusions: "-PLUS" Prehospital Casualty Triage may supplement the strengths of already existing, widely accepted mass-casualty triage strategies. It does not displace START or other rapid initial triage protocols, but in mass-casualty situations with extensive delays in transport, it provides a method to identify under-triage of seriously injured casualties. "-PLUS" also presents a framework for capturing the triage considerations used by experienced medical providers, and so may provide a valuable teaching tool for training future triage professionals. Further research and field assessment is required.